Implementasi Sistem Point of Sale Pada Toko Laguna Painting Kisaran - Dinda Dwi Amara; Fauriatun Helmiah; Santoso Santoso (LPPM STMIK Royal Kisaran, 2022)
Abstract: The rapid development of the business world and increasingly fierce business competition encourage companies to always try to improve the quality of products and services to consumers. Today's business world requires a medium to assist in managing the sales process and recording reports quickly to meet the needs of trading businesses. Laguna Painting Paint Shop is a business engaged in the sale of paint in the Kisaran area. Where in their daily life, Laguna Painting Paint Shop sells paint for both inside and outside the city. Currently the Laguna Painting Paint Shop performs transactions manually in its business processes, this can be seen from the sales transaction process which is calculated and recorded in the sales note paper. To improve the sales system at the Laguna Painting Paint Shop, it is necessary to have an application as a fighter, namely a cashier application or commonly called a POS that can simplify the process of sales transactions and preparing reports. With this POS program, it is hoped that transaction activities will be more effective and efficient at the Laguna Painting Paint Shop. Keywords: point of sale; sale; paint shop Abstrak: Perkembangan dunia bisnis yang semakin pesat dan persaingan usaha yang kian ketat mendorong perusahaan untuk selalu berusaha meningkatkan kualitas produk dan pelayanan kepada konsumen. dunia bisnis saat sekarang ini membutuhkan suatu media untuk membantu dalam mengelola proses penjualan dan pencatatan laporan yang cepat untuk memenuhi kebutuhan usaha dagang. Toko Cat Laguna Painting merupakan suatu usaha yang bergerak di bidang penjualan cat di daerah Kisaran. Dimana dalam kesehariannya, Toko Cat Laguna Painting melakukan penjualan cat untuk dalam kota maupun luar kota. Saat ini Toko Cat Laguna Painting melakukan transaksi secara manual di dalam proses bisnisnya, hal tersebut terlihat dari proses transaksi penjualan dihitung dan dicatat dalam kertas nota penjualan. Untuk memperbaiki sistem penjualan pada Toko Cat Laguna Painting maka perlunya suatu aplikasi sebagai penjuang yaitu aplikasi kasir atau biasa disebut dengan POS yang dapat mempermudah dalam proses transaksi penjualan dan penyusunan laporan. Dengan adanya program POS ini, diharapkan kegiatan transaksi menjadi lebih efektif dan efisien pada Toko Cat Laguna Painting. Kata kunci: point of sale; penjualan; toko cat